Patterns of HIV and syphilis infection in Northern Thailand 1998-2001 - Chris Beyrer (2018)
Northern Thailand has been the epicentre of a largely heterosexually transmitted HIV epidemic that has recently involved married women. In preparation for HIV-prevention trials, we investigated patterns of HIV and syphilis risk through annually measured HIV and syphilis prevalence among northern Thai, peri-urban, community-dwelling men (n = 2564) and women (n = 3907) aged 18-35 years between 1998 and 2001. Crude HIV and syphilis prevalence were 3.3% and 2.7% for men and 2.3% and 2.1% for women, respectively. In logistic regression models of HIV and syphilis, compared with married men/ women, widowers and widows were at increased risk (odds ratio; 95% confidence interval) of syphilis (7.86; 1.56-39.6 and 3.3; 1.14-9.61, respectively) and HIV (12.68; 3.23-49.8 and 41.3; 24.3-70.3, respectively). The oldest women were at lower risk of HIV (0.43; 0.22-0.85). For men and women, those with syphilis were approximately three times more likely to have HIV. These unique population data illustrate evolving sex parity of HIV burden in northern Thailand.